Development and study of the stability of a moisturizing cream based on palm oil (Elaeis guineensis) (Research, Society and Development, 2023)
One of the products derived from palm oil (Elaeis guineenses) is olive oil, extracted from the mesocarp of its fruit, which without refining preserves the bioactives and makes it a potential ingredient in the production of cosmetics. Thus, this study aimed to develop and evaluate the preliminary stability of a palm oil-based moisturizing cream. Three formulations were manipulated for the study: standard formula (FP), anionic based formula (F1) and non-ionic based formula (F2), in the last two, with a concentration of 10% of palm oil. The samples were analyzed for preliminary stability for 28 days, observing organoleptic characteristics (appearance, color and odor) and physical-chemical characteristics (centrifuge test, thermal stress, light radiation, pH, density, freezing and thawing cycle). These tests were carried out in accordance with the ANVISA and Brazilian Pharmacopoeia 5th edition stability guide for cosmetic products. The results obtained in the analysis of creams with 10% palm oil showed stability in the centrifugation, density and pH tests. Regarding the organoleptic characteristics, these formulations maintained the colors of the initial tests. As for the tests of light radiation, heat stress, freezing and thawing cycles, slight changes were observed in F2 while in F1 there were no changes, leading to consider the latter as the most stable for the development of palm oil-based cream. In view of the study, palm oil proved to be a bioactive potential to formulate stable creams, especially with an anionic base, with antioxidant, moisturizing and anti-aging properties.